PEMANFAATAN SISTEM PAKAR LITERATUR REVIEW - Dwi Handoko Putra; Nurabiyyu Rahditiantoro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The digital era has opened up new opportunities in the development and implementation of expert systems in the field of Information Technology (IT). An expert system is a computer-based system that uses specific knowledge and procedures to solve problems at a level comparable to an expert in a particular field. In the digital era, expert systems can utilize abundant data and information to make more accurate and efficient decisions. Technologies such as machine learning and artificial intelligence enable expert systems to learn and adapt to changing environments and conditions. However, challenges such as data security and user privacy are also concerns in the development of expert systems in the digital era. Therefore, it is important to consider these aspects in the design and implementation of expert systems in IT in the digital era. Based on these conditions, the study wants to explore what kind of method approach can be used to detect the use of expert systems. This study uses a survey approach to published papers published during 2020-2024. By conducting this study, we can find out the types of algorithms used for similar research topics. The most popular approach that is most popular according to this study is Classification using Naive Bayes and Certainty factor, and the most media platform is Website.